2003
DOI: 10.1017/s0263574703004946
|View full text |Cite
|
Sign up to set email alerts
|

Swarm robotic odor localization: Off-line optimization and validation with real robots

Abstract: This paper presents an investigation of odor localization by groups of autonomous mobile robots using principles of Swarm Intelligence. First, we describe a distributed algorithm by which groups of agents can solve the full odor localization task more efficiently than a single agent. Next, we demonstrate that a group of real robots under fully distributed control can successfully traverse a real odor plume, and that an embodied simulator can faithfully reproduce these real robots experiments. Finally, we use t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
57
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 40 publications
1
57
0
Order By: Relevance
“…Through real-robot [16] [15] and simulation [14] experiments, we have recently shown that the surge-spiral [6] [7] [2] [4] and the surge-cast [15] algorithms are faster and more reliable than pure casting [11] [10] [23] [13] [12] [1] in laminar wind flow. The experiments were run using a single robot, and the result was in- Thomas Lochmatter, Alcherio Martinoli Distributed Intelligent Systems and Algorithms Laboratory (DISAL),École Polytechnique Fédérale de Lausanne (EPFL), Station 2, 1015 Lausanne, Switzerland.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through real-robot [16] [15] and simulation [14] experiments, we have recently shown that the surge-spiral [6] [7] [2] [4] and the surge-cast [15] algorithms are faster and more reliable than pure casting [11] [10] [23] [13] [12] [1] in laminar wind flow. The experiments were run using a single robot, and the result was in- Thomas Lochmatter, Alcherio Martinoli Distributed Intelligent Systems and Algorithms Laboratory (DISAL),École Polytechnique Fédérale de Lausanne (EPFL), Station 2, 1015 Lausanne, Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-robot odor source localization experiments with an algorithm called spiral surge (which is close to the surge-spiral algorithm used here) have previously been carried out by Hayes et al [6] [7]. Hayes ran experiments with up to 6 real robots, and up to 10 robots in simulation.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, complex systems, such as fish schools or animal herds, can be viewed as information-processing entities with a collective awareness of their environment (7). Understanding their capacity for performing search tasks will have important consequences for the development of distributed technologies, such as olfactory robot swarms, with applications in the detection of explosives, landmines, or locating people in search-and-rescue operations (8)(9)(10).…”
mentioning
confidence: 99%
“…The design outcome can be defined as a group behaviour, and an evolutionary algorithm addresses the hard problem of a solution for the individual robot. Often a simulation is used and provides convenient access to group-level evaluative metrics [16] [14][17] [6] [23].…”
Section: Introductionmentioning
confidence: 99%